Space-time correlation development of the lake levels change during the late glacial and holocene of the Baltic Lake Districts - Novik, Aliaksei A. (Journal of the Belarusian State University. Geography and Geology, 2017)
Inter-regional correlation and comparison of paleogeographic events on the basis of a common methodological approach in the interpretation of geological, geochemical and palaeobotanical data on the example of the Baltic Lake District was carried out. The data obtained from the study of lake sediments are important in paleogeographic reconstructions of past events. Their analysis allowed us to restore the integrity and consistent picture of the dynamics of lake levels as an indicator of the evolutionary history of the natural environment of the region in the last 14 000 years. General patterns of sedimentation and lake level fluctuations are primarily concerned with the global trend of warming in the early post-glacial period, the disappearance of permafrost. Further changes in the character of sedimentation is determined by climatic cycles of the Holocene and the stage of change continental.